Analisis Pengalihan Anggaran Sebagai Solusi Terhadap Hambatan Ekonomi Masyarakat Ponorogo Akibat Covid-19 - Febrian Adi Nugraha; Asis Riat Winarto; Rochmat Aldy Purnomo (Jurnal Pemerintahan dan Politik, 2020)
Ponorogo is one of the many region that is also seriously affected by the COVID-19 outbreak. The purpose of this research aims to analyze related activities made by the Ponorogo government, as an effort to overcome the economic barriers of society due to COVID-19. Based on the reports ang facts in the field, the affected people are those who have not been covered by assistance programs such as PKH or BPNT, around 15.000 people. The method in this research is to find a variety of scientific literature, the latest, and valid form of media coverage, and scientific journals as a reference. Ponorogo government innovates policies by diverting the budget to help the process of the acceleration of handling COVID-19 with the main object is society. The result of this research concluded that the Ponorogo government had succeeded in coordinating and agreeing in the proses of determining the budget diversion policy. The said budget diversion is taken from a number non-priority budgets items, or in other words it can still be delayed. In this researches can be analyzed that of course the budget diversion policy has gone through various considerations ang long-term calculations, so that effort to create economic stability can be carried out as soon as possible. However, what’s need to be underlined is related to how the diversion of budget also creates other impact namely inhibiting development process like infrastructure, housing, settlement, increasing human resources, and so forth.  The priority scale determined by the Ponorogo government in passing the crisis period dua to COVID-19 is a manifestation of the principle of good government, that the basic needs of the society are the biggest responsibility (even more so in the era of disasters). In addition, the status of the red zone in Ponorogo itself doses contribute to additional logical reasons for the government to make diversion budget precisely and directed. This research aims to analyze the diversion of budget, as a solution to the economic constrains of Ponorogo society.  Keywords: Analyze, Diversion, Budget, Economic, COVID-19